2018
DOI: 10.1007/s00415-018-9056-8
|View full text |Cite
|
Sign up to set email alerts
|

Generalization after ocular onset in myasthenia gravis: a case series in Germany

Abstract: The conversion rate in ocular myasthenia was high in our series, predicted by the presence of a thymoma. Our findings suggest that corticosteroids can prevent secondary generalization in ocular myasthenia patients with thymic hyperplasia, which requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 39 publications
7
39
1
Order By: Relevance
“…A small platform was found between 17 and 24 months after disease onset, and the conversion occurred slower after that. Similar deceleration was also found in the study of Li et al [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A small platform was found between 17 and 24 months after disease onset, and the conversion occurred slower after that. Similar deceleration was also found in the study of Li et al [19].…”
Section: Discussionsupporting
confidence: 90%
“…Second, most of the medical data were obtained retrospectively and the follow-up period of patients was not long enough. Third, several studies reported that steroid use is a protective factor and may delay time to the conversion [13,19], but we could not effectively evaluate it because of the small number of patients whose immunosuppressant treatment could be evaluated and the design of this retrospective study. A prospective and controlled study or a well-designed real-world study will provide more valuable information.…”
Section: Discussionmentioning
confidence: 98%
“…In as "ocular or bulbar plus limb muscle weakness", but in the definition of Li et al the presence of limb muscle weakness was not necessary and bulbar weakness alone was sufficient ("symptoms other than ocular symptoms, such as dysarthria, dysphagia, dyspnea or weakness of the jaw, neck or arms and legs"). [9,17] For this reason we avoided the term 'generalized weakness' in our phenotype classification and opted to describe different muscle regions separately.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars indicated positive AChR-Ab, abnormal RNS tests and abnormal SFEMG tests in the early stages of disease could predict more GMG conversion [9,23,24]. While other researches pointed out these factors could not be predictors [8,25].Due to restrictions of earlier objective condition, we did not carry out the AChR-Ab titer detection. In further study, we will take it into consideration.…”
Section: Discussionmentioning
confidence: 95%
“…Both in Korean and Singapore, repetitive nerve stimulation (RNS) tests and antiacetylcholine receptor antibody (AChR-Ab) could be predictive factors for conversion of OMG to GMG [6,7]. While in a Germany study, the scholar deemed the presence of thymoma was the only risk factor for secondary generalization [8].…”
Section: Introductionmentioning
confidence: 99%